Population change and socio-economic dynamics of the municipalities of Boyaca - Casas-Herrera, Julián Augusto; Gil-León, José Mauricio; Forero-Medina, María Hulima (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This paper outlines some causes that originated the population change in the municipalities of Boyacá from 1993 to 2005. According to the theory of polarization there are territories that thanks to their economic dynamics attract the population surrounding them. To analyze the above information, the population censuses of DANE of the years indicated for Colombia was taken into account. The paper concludes by pointing out that the processes of regional economic development are the main generators of the change and population dynamics, experienced by the municipalities of the department, showing that the municipalities with the worst socioeconomic conditions tend to be expelling the population; while those who present better conditions are becoming attractive or receptive axes of population, which poses to the big cities to solve problems of urban planning and the territorial reordering.